PENGARUH LATIHAN RELAKSASI PROGRESIF UNTUK MENCEGAH KEKAMBUHAN ASMA BRONKIAL - Fajar, Berliano; Kristianawati, Kristianawati (Indonesian Journal of Nursing Health Science, 2017)
AbstractBackground: Bronchial asthma is a chronic disease that causes the top five deaths in the world. Theprevalence of bronchial asthma in Indonesia by 2025 is 400 million with 225,000 dead. One way to prevent relapse in people with bronchial asthma by doing progressive relaxation exercises regularly for one  week. This study aims to determine the effect of progressive relaxation training on the decrease in recurrence rate in patients with bronchial asthma in the working area of West Jakarta Kebon Jeruk subdistrict health center. The sample used is bronchial asthma as many as 20 people with purposive sampling technique.  The method used is Pre-Experiment, pre test, post test without control group. Result: Paired t-test analysis result, got decrease of asthma recurrence rate p  =0,000   (p  <0,005).  Conclusion:  There  was  a  significant  effect  between  the  recurrence  rate  of bronchial  asthma  before  and  after  the  provision  of  progressive  relaxation  exercises.  It  is recommended for bronchial asthma clients in the working area of West Jakarta Kebon Jeruk subdistrict health center to apply physical exercise by performing regular progressive relaxation on bronchial asthma clients to decrease / prevent recurrence of bronchial asthma. Keywords: influence, progressive relaxation, recurrence of asthma AbstrakLatar belakang: Asma bronkial adalah penyakit kronis yang menyebabkan lima kematian teratas didunia. Prevalensi asma bronkial di Indonesia pada tahun 2025 adalah 400 juta dengan 225.000 orang meninggal. Salah satu cara untuk mencegah kambuh pada penderita asma bronkial dengan melakukan latihan relaksasi progresif secara teratur selama satu minggu. Penelitian ini bertujuan untuk mengetahui pengaruh latihan relaksasi progresif terhadap penurunan tingkat kekambuhan pada pasien asma bronkial di wilayah kerja Puskesmas Kecamatan Kebon Jeruk Jakarta Barat. Sampel yang digunakan adalah asma bronkial sebanyak 20 orang dengan teknik purposive sampling. Metode yang digunakan adalah Pre-Experiment, pre test, post test tanpa kelompok kontrol. Hasil: Hasil analisis t- test paired, didapatkan penurunan tingkat kekambuhan asma p = 0,000 (p <0,005). Kesimpulan: Ada pengaruh yang signifikan antara tingkat rekurensi asma bronkial sebelum dan sesudah pemberian latihan relaksasi progresif. Direkomendasikan untuk klien asma bronkial di wilayah kerja Puskesmas Kecamatan Kebon Jeruk Jakarta Barat untuk menerapkan latihan fisik dengan melakukan relaksasi progresif secara teratur pada klien asma bronkial untuk mengurangi / mencegah terulangnya asma bronkial. Kata kunci: pengaruh, relaksasi progresif, rekurensi asma